VULNERABILIDADE NATURAL À PERDA DE SOLO NA BACIA HIDROGRÁFICA DO RIO FORMOSO, BONITO-MS - KASSIA RAYLENE SOUSA DA SILVA (2023)
The diagnosis of natural vulnerability to soil loss in watersheds enables the analysis of the physical characteristics of its landscape units, besides establishing the degrees of vulnerability for its environmental variables, and can be used to support environmental zoning and decision-making. The objective of the present work was to diagnose the natural vulnerability to soil loss in the Rio Formoso watershed, in order to subsidize the environmental zoning of the region. The methodology used was the one developed by Crepani et al. (2001), which is based on the concept of Ecodynamics by Tricart (1977) to analyze the morphogenesis/pedogenesis relationship and, based on this, establishes criteria for the diagnosis of the environmental fragility of an area in relation to erosive processes. Thus, in this research, first there was a bibliographic survey, where relevant works in the area were searched; then a survey of the necessary geospatial data in vector and matrix formats was carried out, and later this information was worked in QGIS 3.10, mapping the Basic Territorial Units (geology, soils, vegetation, climate, relief) and their respective degrees of vulnerability. Finally, the vulnerability overlay was made for the UTB, which resulted in the natural vulnerability to soil loss chart for the Formoso River watershed. The analysis of natural vulnerability to soil loss in the Rio Formoso watershed revealed that the study area has, predominantly, areas with Median Stable/Vulnerable terrain, in 53.56% of its extension. The Moderately Stable class is the second largest in the watershed, occupying 459.62 km² (34.93%), while the Moderately Vulnerable and Stable classes are less expressive, occupying, respectively 146.20 km² (11.11%) and 5.22 km² (0.40%). The study area did not present any land classified as Vulnerable. The Rio Formoso watershed predominantly showed environments with medium fragility to suffer erosion processes, demonstrating a certain balance in the morphogenesis/pedogenesis relationship. At the same time, terrains closer to stability (Moderately Stable) were also quite expressive, occupying the second largest area of the basin, which may indicate that the watershed has a complexity for the vulnerability of its physical environments.